ISOLASI NANOSELULOSA DARI TANDAN KOSONG SAWIT MENGGUNAKAN HIDROLISIS ASAM SEBAGAI MATERIAL BIOMEDIS - Ayu Syufiatun Tarigan (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2021)
This study aims to isolate nanocellulose from oil palm emptry fruit bunches (OPEFB) using acid hydrolysis method. Hydrolysis was carried out for 2 hours using 10% HCl and followed by centrifugation, ultrasonication and dialysis using a semipermeable membrane. The results obtained were tested by FT-IR, and it was found that there was a -OH functional group at a wavenumber between 3000-3500 cm-1, a C-H group in the area 2850-3000 cm-1, -CH2 bending at a wavenumber 1330-1465 cm-1 and the CO group at wave numbers 1000-1100 cm-1. This indicates that the product is in the form of cellulose. The particle size distribution of cellulose was tested with a PSA (Particle Size Analyzer) and the nanocellulose was about 7.2 nm in size.